Serial pharmacological prescribing practices for tic management in Tourette syndrome. (24th August 2015) - Farag, Mena; Stern, Jeremy S.; Simmons, Helen; Robertson, Mary M.
Abstract : Pharmacological treatments for Tourette syndrome (TS) vary in efficacy between different patients. The evidence base is limited as even high quality controlled studies tend to be of relatively short duration which may lose relevance in clinical usage. Patients are frequently treated with serial agents in the search for efficacy and tolerability. The success of this strategy has not been previously documented. We examined 400 consecutive TS patients seen over a 10‐year period, some with a longer prior history in other clinics; 255/400 (64%) were prescribed medication. We present this heterogeneous cohort in terms of the number of drugs they had tried, and as a proxy measure of some benefit of the last drug used, whether it had been prescribed under our supervision for ≥5 months. The most commonly prescribed medications were aripiprazole (64%), clonidine (40%), risperidone (30%) and sulpiride (29%) with changes in prescribing practises over the period examined. The number of different drugs tried were one (n = 155), two (n = 69), three (n = 36), four (n = 14), five (n = 15), six (n = 5), seven (n = 2) and eight (n = 1). The data illustrate the difficulty in drug treatment of tics and suggest that even after trials of several agents there is potential benefit in trying further options. Copyright © 2015 John Wiley & Sons, Ltd.